Design of Data Security for Remote Access Using IPsec- and SSL-Based VPN - Ahmad Fikri (Institute of Information Technology and Social Science (IITSS), 2025)
The rapid advancement of digital communication technologies has increased the need for secure remote access within corporate environments. This study develops and implements a secure network architecture for PT Tanjungenim Lestari Pulp & Paper using Virtual Private Network (VPN) mechanisms based on Internet Protocol Security (IPsec) and Secure Socket Layer (SSL). The existing network, which utilizes a star topology and file-sharing mechanisms, was found to lack sufficient security, particularly in protecting data transmission to external partner companies. The proposed system integrates IPsec-based VPN tunneling to ensure encrypted communication channels and SSL certificates to safeguard FTP authentication processes. Data were collected through action research and document studies, followed by network design, IP addressing, router configuration, VPN deployment, FTP server installation (VSFTPD), and file transfer testing. The results demonstrate successful establishment of secure tunnels, encrypted data exchange, and protection against credential interception during authentication. This study concludes that implementing IPsec VPN and SSL-secured FTP significantly enhances remote access security, maintains data confidentiality, and strengthens the overall network infrastructure of PT Tanjungenim Lestari Pulp & Paper.